Substrate-dependent reduction of a recombinant chromaffin granule Cyt-b561 and its R72A mutant - Lakshminarasimhan, Mahadevan; Bérczi, Alajos; Asard, Han (Acta Biologica Szegediensis, 2006)
Cytochrome b561 (Cyt-b561) proteins constitute a family of integral membrane proteins, catalyzing ASC-driven trans-membrane electron transport. Numerous isoforms of Cytb561 are present in invertebrates, vertebrates, and plants. The only protein of this family, however, which has been characterized in details at both biophysical, biochemical and physiological levels so far, is the bovine chromaffin granule Cyt-b561 (CGCyt-b561). Recently, both the bovine and the mouse CGCyt-b561 has been expressed in yeast cells and the recombinant proteins were shown to have biophysical properties similar to the native bovine CGCyt-b561. We have expressed the mouse CGCyt-b561 with a His6 -tag at the C terminus (CGCyt-b561(C6H)) in yeast (Saccharomyces serevisiae) cells and studied the reduction of CGCyt-b561(C6H) in the presence of different natural reducing agents. Besides the well-known natural reductant ascorbate (ASC) and the often-used artificial reductant dithionate, NADH, GSH, and dihydrolipoic acid (DHLA), also reduced the fully oxidized protein. Interestingly however, NADPH was not effective at all. When the same reductants were tested with the R72A mutant of CGCyt-b561(C6H), a mutant with impaired ASC-dependent reducibility, neither pyridine-dinucleotides could reduce the R72A mutant. DHLA-dependent and ASC-dependent reduction kinetics were very similar in case of the R72A mutant but differed in case of CGCyt-b561. These results raise the question of how many natural reductants the CGCyt-b561 may utilize in vivo.